Biosecurity in the handling and disposal of remainders in the odontology attention centers in the north Zone of Lima city 2005 - Velazco Mendívil, Augusta (2009)
The objective of the study descriptive and transversal was to determinate if the solid remainders produces in the odontology private offices are treated and adecuatly disposed. A descriptive and transversal study was undertaken. The group was constituted of all odontology private offices, in the North Zone of Lima city, constituted by the following districts: Los Olivos, Comas, Independencia, Rimac, San Martin de Porres, Carabayllo and Puente Piedra. According to the register in the Odontology association of Lima and considering the geografical area of the distribution of the space according to INEI and the ministerial resolution of the technique norms: “Procedures for the Handling of Hospital Solid Residuals” (R.M.N°217-2004/MINSA), the surgeons dentists that worked in the respective odontology office during February, March and April, 2005 were visited a 153 dentists. A Registration of Record was applied for Interviews and Observations. The personnel who worked at the odontology office were interviewed, it was checked if the biosegurity norms and eliminations of the solid remainders were adequately achieved by the workers. The study variables were: Sex, Time of Professional Exercise and use of biosegurity elements: if the operator used gloves and mask, if the assistant used gloves and mask, if the patient was put a bib on; Elimination of Remainders: if they used bags in the garbage, if they used special containers for puncture sharp materials and if they used red bags for residuals biocontaminates. The kind of transport that they used for eliminating the remainders. Garbage trucks or informal and if the recolectors selected or joined the office residuals. Final disposition: Sanitary filler or open garbage dump. The study determined that only 20,3 % used pots for sharp cutting material, it was not found red bags in the trash can for biocontamined materials,13,7 % of solid residue were thrown to open garbage dump. In conclusion, technical norms are not complied in the final disposition of solid residue, dental offices do not eliminate nirtrate adequately their residues and products of dental care.